Interim Analysis of Impact of Adding Low Dose Pulmonary Radiotherapy to Moderate COVID-19 Pneumonia Patients: IMpaCt-RT Study - Singh, Pritanjali; Mandal, Avik; Singh, Dharmendra; Kumar, Subhash; Kumar, Amarjeet; Rakesh, Amrita; Ranjan, Rakesh; Verma, Manika; Rai, Deependra Kumar; Bhushan, Divendu; Shankar, Abhishek; Sinha, Arkaprava; et al. (Frontiers in Oncology, 2022)
Abstract Purpose: Treatment for coronavirus disease 2019 (COVID-19) pneumonia remains largely supportive till date and multiple clinical trials took place within the short span of time to evaluate the role of investigational therapies. The anti-inflammatory effect of low dose whole lung radiation in treating pneumonia has been documented earlier. This clinical trial analyzed the efficacy of low dose radiation therapy (LDRT) to stop conversion of moderate COVID-19 pneumonia disease into severe category. Methods: After getting clearance from the Institutional ethical committee this trial got registered with the Central Drugs standard control Organization India (ECR/1387/Ins/BR/2020) and Clinical Trials Registry-India (CTRI/2021/06/033912, 25th May 2021). Patients with moderate COVID-19 pneumonia as characterized by Ministry of health and family welfare (MOHFW) Government of India, were randomized (1:1) to low dose whole lung radiation versus no radiation. All patient’s treatment were concurrently being given as per institutional protocol. Patients were followed up with clinical and laboratory parameters monitored on Day 1, 3, 7 and day14. Computed tomography scan (CT scan) of thorax was performed on Day 1 and Day 7. Patients were evaluated for conversion of moderate into severe disease as per National Early Warning Score-2 (NEWS-2 score) as the primary end point. The secondary endpoints included changes in ratio between peripheral capillary oxygen saturation and fraction of inspired oxygen (SpO2/FiO2), biochemical markers, 25-point CT severity score, and radiation induced acute pulmonary toxicities. Result: At the interim analysis, there were seven patients in the radiation arm and six in the control. Whole lung LDRT improved outcome of SpO2/FiO2 at Day 3, however it did not convert into statistically significant improvement for NEWS-2 score. LDH showed significant reduction in RT arm (p=0.015) at day 3, however other secondary endpoints revealed no significant difference between the two arms at day3, day7, and day14. Conclusion: LDRT seems to have the potential to prevent moderate COVID-19 pneumonia from deteriorating to severe category. However, further randomized clinical trial with adequate number of such patients is warranted to establish the definitive role of LDRT in the management of COVID-19 pneumonia.